Implementasi Psikospiritual Islam Dalam Pembentukan Model Motivasi Pembangunan Diri Remaja: Islamic Psychospiritual Implementation in Motivational Model of Adolescents’ Self-Development - Paad, Nur Shahidah; Syed Muhsin, Sharifah Basirah; Zainal Abidin, Mohd Syukri (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Self-development is a lifelong process. The various negative influences and the abandonment of the psychospiritual aspect contribute to the volatile and declining motivation among the teenager, which later would obstruct their self-development process. Therefore, this research will propound solutions to the preceding issue by utilizing qualitative research design via content analysis. The finding indicates that the motivation intervention for the teenager’s self-development is complex and involves varying elements related to the informant self, spiritual, as well as social context. On that account, this research suggests a supplementary model of motivation that is more systematic and characterized with Islamic concept that corresponds with their psychological needs. Also, this model incorporates the fundamental element of Islamic psychospiritual such as akhlaq (virtue), the potential of al-ruh (soul), tazkiyah al-nafs (purification of the heart), and intention for the self-development of the teenager.